TRADITIONAL USES OF HERBAL MEDICINAL PLANTS OF RAJASHTHAN: GUGGAL: Life Science-Ethno botany - SHARMA, SANTOSH; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Guggal (Commiphora wightii (Arn.) Bhandari) (Burseraceae) is distributed in tropical and sub-tropical regions. It is small shrub with sessile leaves. Three sterols gugglusterols I, II and III, two sterones and two dieterpines are found. Gum and bark is useful to treat obesity, arthritis, indolent and ulcers. Guggul is used in various ways to cure different ailments like gonorrhoea, pyorrhoea, ulcers, piles, asthma, cough, hernia and leucoderma.